Penyuluhan tentang Pengenalan dan Penggunaan Obat Tradisional (Herbal Medicine) - Ema Ratna Sari; Nilda Lely; Erjon Erjon; Masayu Azizah; Agnes Rendowaty; Ade Arinia Rasyad; Dewi Patmayuni; Lilik Pranata; Masayu Rosyidah (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The introduction and use of traditional medicine is an alternative step to carry out natural and effective treatment. Traditional medicine has great potential to improve people's health. Not many people use herbs for medicinal purposes, so the community service activity team aims to increase knowledge about Traditional Medicine (Herbal Medicine), especially for teenagers. Currently, teenagers prefer to use modern medicine, so their knowledge and experience regarding traditional medicine are still very lacking. Knowledge about herbal medicine is important for teenagers because it can help them use traditional medicine appropriately. Good knowledge of herbal medicine can also help prevent traditional medicine that can heal from becoming dangerous. The activity method is carried out using education through counseling about the introduction and use of traditional medicine (Herbal Medicine), which is carried out for students at Ummul Quro Al-Hamidiyah Foundation Middle School, Masjid Kyai Muara Ogan Street, Kertapati Palembang. This activity was held on December 19, 2024, with 50 participants from Ummul Quro Al-Hamidiyah Foundation Middle School students. The activity results stated that students understood the counseling about using traditional medicine (Herbal Medicine) well.